2016
DOI: 10.1155/2016/4519846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outflow StructuresIn Vivoafter the Phacocanaloplasty

Abstract: Purpose. To evaluate the in vivo changes in Schlemm's canal (SC) and the trabecular meshwork (TM) in patients with primary open-angle glaucoma (POAG) after phacocanaloplasty using anterior segment optical coherence tomography (AS-OCT). Methods. Ten eyes of nine patients with POAG (6 men and 3 women) who underwent phacocanaloplasty. Preoperative and postoperative visual acuity (VA), intraocular pressure (IOP), and use of glaucoma medications were evaluated. The main outcome measures were the area of SC and TM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…Wang et al showed that there was a significantly reduced cross‐sectional area of Schlemm's canal in patients with primary open angle glaucoma . Studies from 2016 also demonstrated that the size of Schlemm's canal increased in patients post‐canaloplasty, an increase that correlated with a decrease in intraocular pressure …”
Section: Resultsmentioning
confidence: 94%
“…Wang et al showed that there was a significantly reduced cross‐sectional area of Schlemm's canal in patients with primary open angle glaucoma . Studies from 2016 also demonstrated that the size of Schlemm's canal increased in patients post‐canaloplasty, an increase that correlated with a decrease in intraocular pressure …”
Section: Resultsmentioning
confidence: 94%
“…2) [20,21]. Dadurch kann der Einfluss medi-kamentöser Therapien [22,23] und operativer Verfahren, wie Kataraktextraktion oder Kanaloplastik, auf die Schlemm-Kanal-Anatomie untersucht werden [24,25]. So wurde gezeigt, dass die Applikation von Prostaglandinaugentropfen zu einer Dilatation des Schlemm-Kanals führt, was auf eine frühe trabekuläre Wirkkomponente der Tropfen hinweist [22].…”
Section: Schlemm-kanalunclassified